Conventional IBS block system in ULS of cyclic loading - Tee, Chen Po, 1991- , author; Abdul Kadir Marsono, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2015